السلوك الاجتماعي ضمن بعض الاحياز الداخلية والجوارية للاسكان الافقي المخطط لذوي الدخل المحدود في المنطقة العربية (Journal of Planner and Development, 2012)
This is an attempt to assess the most common forms of internal and neighboring spaces of horizontal Housing among low-income people in cities of Arab countries to see the extent to which they meet the requirements and facilities of social behavior within those spaces. To achieve this, the study adopts a method based on the premises of housing planning. The foundations that have contributed, with their impact, to the selection of design patterns of housing are addressed besides the anatomy of horizontal projection models with clarification of their advantages and disadvantages by exploring the views of a sample selected in two inhabited areas in Greater Khartoum regarding how housing spaces meet social activities including the design of housing, neighboring space, services, streets, and the level of a forestation. Then the findings of the field study are reviewed and most important results are recorded with a proposal of recommendations for the formulation and development of forms of horizontal housing followed in Arab cities, including the treatment of residential neighborhood as living spatial entity, preparing strategies to systematically take social behavior and other dimensions in housing planning, and to take sustainability as a style and approach in the implementation of projects.